Boosting recovery rather than buffering reactivity: Higher stress-induced oxytocin secretion is associated with increased cortisol reactivity and faster vagal recovery after acute psychosocial stress. (December 2016) - Engert, Veronika; Koester, Anna M.; Riepenhausen, Antje; Singer, Tania
Highlights: Blood oxytocin levels are reliably increased after psychosocial stress in healthy men and women. Stress-induced oxytocin secretion is not linked to lower cortisol stress reactivity. To the contrary, the higher stress-induced oxytocin secretion, the higher cortisol stress reactivity. However, in the second phase of the stress response, higher oxytocin secretion is associated with faster vagal recovery. Abstract: Animal models and human studies using paradigms designed to stimulate endogenous oxytocin release suggest a stress-buffering role of oxytocin. We here examined the involvement of stress-induced peripheral oxytocin secretion in reactivity and recovery phases of the human psychosocial stress response. Healthy male and female participants ( N  = 114) were subjected to a standardized laboratory stressor, the Trier Social Stress Test. In addition to plasma oxytocin, cortisol was assessed as a marker of hypothalamic-pituitary-adrenal (HPA-) axis activity, alpha-amylase and heart rate as markers of sympathetic activity, high frequency heart rate variability as a marker of vagal tone and self-rated anxiety as an indicator of subjective stress experience. On average, oxytocin levels increased by 51% following psychosocial stress. The stress-induced oxytocin secretion, however, did not reduce stress reactivity. To the contrary, higher oxytocin secretion was associated with greater cortisol reactivity and peak cortisol levels in both sexes. In the second phase of the stress response the opposite pattern was observed, with higher oxytocin secretion associated with faster vagal recovery. We suggest that after an early stage of oxytocin and HPA-axis co-activation, the stress-reducing action of oxytocin unfolds. Due to the time lag it manifests as a recovery-boosting rather than a reactivity-buffering effect. By reinforcing parasympathetic autonomic activity, specifically during stress recovery, oxytocin may provide an important protective function against the health-compromising effects of sustained stress.